Hydrogen production performance and theoretical mechanism analysis of chain-like ZnO/ZnS heterojunction. (8th January 2023) - Qiao, Fen; Liu, Wenjie; Yang, Jing; Yuan, Jiaren; Sun, Kaiyue; Fei Liu, Peng
Abstract: High recombination probability of photo-generated carriers restricts the characteristics improvement of semiconductor photocatalysts. The construction of heterojunction structure has become a common strategy to enhance the transport properties of carriers in catalysts. In this paper, the chain-like structure of ZnO/ZnS heterojunction was prepared by the combination of electrospinning and ion exchange. The composition and structure of ZnO/ZnS composites were studied by SEM, HRTEM, XRD, etc., and the influence of vulcanization degree on the hydrogen production of ZnO/ZnS was studied. Compared with bare ZnO, the chain-like ZnO/ZnS heterojunction shows better photocatalytic hydrogen production performance. When the Na2 S concentration was 0.064 M, the hydrogen production of ZnO/ZnS exhibits the best performance (1140.64 μmol. g −1 ). Proper vulcanization treatment to construct ZnO/ZnS heterojunction structure is the key factor to boost the hydrogen generation performance. The signification enhancement of photocurrent response was observed in ZnO/ZnS composites, which also confirmed the effective charge transfer between ZnO and ZnS. In addition, the charge transfer mechanism and photocatalytic hydrogen production at the ZnO/ZnS interface was discussed by the density functional theory (DFT) calculation. It was also confirmed that the electrons distribution near the interface of ZnO/ZnS heterojunction accelerates the carrier transport of carriers, so that larger electrons and holes are involved in oxidation and reduction, thus enhancing the photocatalytic hydrogen production activity of catalysts. This work provides practical reference value for the design of new composite photocatalyst and the study of catalytic mechanism. Graphical abstract: The chain-like structure of ZnO/ZnS heterojunction was successfully synthesized through electrospinning and ion exchange methods. It is verified that the structure of ZnO/ZnS heterojunction is helpful to promote carrier transport at the interface and realize effective charge transfer. Combined with DFT theoretical calculation, through in-depth analysis of the interface structure change and charge transport performance, the electronic structure of heterojunction structure promotes the separation of photo-generated carriers and the charge transfer, and the corresponding performance of hydrogen production is also greatly improved. Image 1 Highlights: The chain-like structure of ZnO/ZnS was synthesized by the combination of electrospinning and ion exchange treatment. Proper vulcanization treatment can boost the hydrogen generation performance of ZnO. The mechanism of charge transfer and hydrogen production was discussed by DFT calculation.